Prostate perfusion mapping using Fourier‐transform based velocity‐selective arterial spin labeling: Choice of cutoff velocity and comparison with brain - Liu, Dapeng; Zhu, Dan; Xu, Feng; Sedaghat, Farzad; Qin, Qin (Magnetic resonance in medicine, 2023)
Purpose To develop velocity selective arterial spin labeling (VSASL) protocols for prostate blood flow (PBF) and prostate blood volume (PBV) mapping. Methods Fourier‐transform based velocity‐selective inversion and saturation pulse trains were utilized in VSASL sequences to obtain blood flow and blood volume weighted perfusion signal, respectively. Here four cutoff velocities (Vcut = 0.25, 0.50, 1.00, and 1.50 cm/s) for PBF and PBV mapping sequences were evaluated with a parallel implementation in brain for measuring cerebral blood flow (CBF) and cerebral blood volume (CBV) with identical 3D readout. This study was performed at 3T on eight young and middle‐aged healthy subjects comparing both perfusion weighted signal (PWS) and temporal SNR (tSNR). Results In contrast to CBF and CBV, the PWS of PBF and PBV were rather unobservable at Vcut of 1.00 or 1.50 cm/s and both PWS and tSNR of PBF and PBV considerably increased at the lower Vcut, indicating that blood moves much slower in prostate than in brain. Similar to the brain results, the tSNR of PBV‐weighted signal was about two to four times over the corresponding values of PBF‐weighted signal. The results also suggested a trend of reduced vascularity within prostate during aging. Conclusion For prostate, a low Vcut of 0.25–0.50 cm/s seemed necessary for both PBF and PBV measurements to obtain adequate perfusion signal. As in brain, PBV mapping yielded a higher tSNR than PBF.